Risk factors associated with the prevalence of Shiga-toxin-producing Escherichia coli in manured soils on certified organic farms in four regions of the USA - Pires, Alda F. A.; Ramos, Thais De Melo; Baron, Jerome N.; Millner, Patricia D.; Pagliari, Paulo H.; Hutchinson, Mark; Haghani, Viktoria; Aminabadi, Peiman; Kenney, Annette; Hashem, Fawzy; Martínez-López, Beatriz; Bihn, Elizabeth A.; et al. (Frontiers in Sustainable Food Systems, 2023)
Biological soil amendments of animal origin (BSAAO), including untreated amendments are often used to improve soil fertility and are particularly important in organic agriculture. However, application of untreated manure on cropland can potentially introduce foodborne pathogens into the soil and onto produce. Certified organic farms follow the USDA National Organic Program (NOP) standards that stipulate a 90- or 120-day interval between application of untreated manure and crop harvest, depending on whether the edible portion of the crop directly contacts the soil. This time-interval metric is based on environmental factors and does not consider a multitude of factors that might affect the survival of the main pathogens of concern. The objective of this study was to assess predictors for the prevalence of Shiga-toxin-producing Escherichia coli (non-O157 STEC) in soils amended with untreated manure on USDA-NOP certified farms. A longitudinal, multi-regional study was conducted on 19 farms in four USA regions for two growing seasons (2017-2018). Untreated manure (cattle, horse, poultry), soil, and irrigation water samples were collected and enrichment cultured for non-O157 STEC. Mixed effects logistic regression models were used to analyze the predictors of non-O157 STEC in the soil post-manure application. Results show that farm management practices (previous use with livestock, presence of animal feces on the field, season of manure application) and soil characteristics (presence of generic E. coli in the soil, soil moisture, sodium) increased the odds of STEC-positive soil samples. Manure application method and snowfall decreased the odds of detecting STEC in the soil. Time-variant predictors (year and sampling day) affected the presence of STEC. This study shows that a single metric, such as the time interval between application of untreated manure and crop harvest, may not be sufficient to reduce the food safety risks from untreated manure, and additional environmental and farm-management practices should also be considered. These findings are of particular importance because they provide multi-regional baseline data relating to current NOP wait-time standards. They can therefore contribute to the development of strategies to reduce pathogen persistence that may contribute to contamination of fresh produce typically eaten raw from certified farms using untreated manure.